Subthalamic Deep Brain Stimulation Lead Asymmetry Impacts the Parkinsonian Gait Disorder - Schott, Frederik P.; Gulberti, Alessandro; Pinnschmidt, Hans O.; Gerloff, Christian; Moll, Christian K. E.; Schaper, Miriam; Koeppen, Johannes A.; Hamel, Wolfgang; Pötter-Nerger, Monika (Frontiers in Human Neuroscience, 2022)
Abstract Background: The preferable position of Deep Brain Stimulation (DBS) electrodes is proposed to be located in the dorsolateral subthalamic nucleus (STN) to improve general motor performance. The optimal DBS electrode localization for the postoperative improvement of balance and gait is unknown. Methods: In this single-centre, retrospective analyses, 66 Parkinson´s disease (PD) patients (24 female, age 63 ± 7 years) were assessed pre- and postoperatively (8.45 ± 4.2 months after surgery) by using MDS-UPDRS, freezing of gait (FoG) score, Giladi’s gait and falls questionnaire and Berg balance scale. The clinical outcome was related to the DBS electrode coordinates in x, y, z plane as revealed by image-based reconstruction (SureTuneTM). Binomial generalized linear mixed models with fixed-effect variables electrode asymmetry, parkinsonian subtype, medication, age class and clinical DBS induced changes were analysed. Results: STN-DBS improved all motor, balance and FoG scores in MED OFF condition, however there were heterogeneous results in MED ON condition. DBS electrode reconstructed coordinates impacted the responsiveness of axial symptoms. FoG and balance- responders showed slightly more medially located STN electrode coordinates and less medio-lateral asymmetry of the electrode reconstructed coordinates across hemispheres compared to non-responders. Conclusions: DBS electrode reconstructed coordinates, particularly electrode asymmetry on the medio-lateral axis affected the postoperative responsiveness of balance and FoG symptoms in PD patients.